PKM PEMASARAN SOSIAL MEDIA BERBASIS MOBILE DALAM RANGKA MEMBANTU KETERBATASAN RUANG GERAK SELAMA PANDEMI COVID-19 - Miguna Astuti Nina; Nurhafifah Matondang (Universitas Lancang Kuning, 2021)
Partners in PKM are the PAGODA Women's Group (KWP) in Kp. Cigundi, Kec Cibadak, Lebak, Banten. But the condition Kp. Cigundi itself is still quite alarming. Most of the Mitra members have cell phones with access, but Partners have not used HP to promote their Groups, Villages and Enye-Enye products. Partners in this program produce Enye-Enye in a semi-finished form that is packaged simply, Mitra does not produce Enye-Enye for commercial purposes. Enye-Enye has also been recognized as a typical product of the village of Mekaragung, but the income from Enye-Enye products is not obtained because the Partners intentionally sell, so it can be concluded in the early PKM namely a high level of participation from the Mekaragung village office and the community who have MSME businesses that fully support the PKM, the Training and Assistance that is carried out runs and has a lot of experience and heightened enthusiasm KWP Ladies, Pagoda Women's Group to increase knowledge, have increased skills and have increased income for their businesses.